Regional Economies: Divergence in Activity and Convergence in Development - Dumlao, Luis F. (Kasarinlan: Philippine Journal of Third World Studies; Vol 25 No 1-2 (2010): Political Economy of Ideas, 2010)
The disparity between regional differences in economic activity and economic development is emphasized. Lack of convergence in economic activity is more obvious though this is not necessarily bad for there is reason to support a certain degree of divergence. Lack of convergence in economic development is less obvious though its absolute convergence is more necessary for national development’s sake. It is argued that raising the level of infrastructure is the long-run solution towards ultimate convergence in development. However, construction of such, by nature, takes time so that at the moment, the current low level of infrastructure becomes a short-run constraint. This leaves raising awareness toward short-run economic conditions and activities especially to prospective investors as one solution. This can be done using proposed short-run indicators that should be treated with caution.
Keywords: regional economies; Philippines; economic development; economic activity; convergence; divergence; indicators